A preliminary study on biometric watermarking for offline handwritten signature - Low, C. Y.; Teoh, Andrew B. J.; Tee, Connie (2007)
This paper presents a preliminary study on biometric watermarking by using offline handwritten signature. Specifically, offline handwritten signature is discritized into binary bit string as hidden biometric watermark. It is reconstructed subsequently with the intention to authenticate the claimed source of the digital document In this paper, we focus on the study in examining the strength and robustness of three selected biometric watermarking schemes, namely Least Significant Bit (LSB) substitution, CDMA spread spectrum in spatial domain and CDM-A spread spectrum in Discrete Wavelet Transform (DWT), against JPG compression. We check the distortion rate for the original and the extracted biometric bit string after JPG compression. The performance of the selected biometric watermarking schemes is validated based on human visual inspection, Peak Signal to Noise Ratio (PSNR) and distortion rate (normalized Hamming distance). Experiment results show that CDMA spread spectrum in DWT is the most promising scheme in biometric watermarking.